An analysis of the latent classification and influencing factors of the characteristic symptoms in patients with maintenance hemodialysis - FENG Meiqin; CHEN Hongfang; ZHANG Jiayang; ZHANG Layin (Yixue xinzhi zazhi)
Objective To explore the potential subgroups of symptom characteristics and their influencing factors in maintenance hemodialysis (MHD) patients.Methods Patients with MHD in the hemodialysis department of Shaanxi Provincial Hospital of Chinese Medicine from November 2023 to April 2024 were selected by convenience sampling method, and survyed with the general data questionnaire and Dialysis Symptom Index. Mplus 8.3 was used for latent profile analysis of group symptoms, and binary Logistic regression was used to analyze the influencing factors of symptoms group.Results A total of 211 cases of MHD patients were included and divided into two groups: low symptom burden group (39%) and high symptom burden group (61%) according to their symptom characteristics. The results of regression analysis showed that gender[OR=0.189, 95%CI(0.080, 0.446)], age[OR=1.085, 95%CI(1.048, 1.124)]and serum sodium [OR=0.862, 95%CI(0.774, 0.959)]were the influencing factors that distinguished the two subgroups (P ﹤0.05).Conclusion  There is heterogeneity in the symptom characteristics of MHD patients, which can be divided into two potential subgroups. Medical staff should pay more attention to female patients, elderly patients, and patients with serum sodium levels less than 138.46 mmol/L.